A Spectral Method for Second Order Volterra Integro-Differential Equation with Pantograph Delay (Advances in Applied Mathematics and Mechanics, 2013)
In this paper, a Legendre-collocation spectral method is developed for thesecond order Volterra integro-differential equation with pantograph delay. We providea rigorous error analysis for the proposed method. The spectral rate of convergencefor the proposed method is established in both $L^2$-norm and $L^∞$-norm.